Trypanocidal Activity of Flavokawin B, a Component of Polygonum ferrugineum Wedd - Rodrigues, Danilo F.; Maniscalco, David A.; Silva, Flavia A. J.; Chiari, Bruna G.; Castelli, María V.; Isaac, Vera L. B.; Cicarelli, Regina M. B.; López, Silvia N. (Planta Medica, 2017)
The trypanocidal potential of the natural chalcone flavokawin B, which was isolated from the hexanic extract of Polygonum ferrugineum Wedd., is reported here. Although flavokawin B is widespread, this is the first report about its trypanocidal properties on both Trypanosoma cruzi (IC50 = 9.5 µM, IC50 = 34.7 µM benznidazol, Y strain) epimastigotes and Trypanosoma brucei (IC50 = 4.8 µM, IC50 = 6.4 µM pentamidine, 29–13 strain) procyclic forms, which was also corroborated on T. brucei strain 427 (IC50 = 6.2 µM). In order to learn more about its properties, unspecific cytotoxicity on Hep G2 cells was investigated as well as the trans-splicing inhibitory potential on T. brucei cells. The results shown here point to flavokawin B as a candidate in the search for new agents. It is also cheaper and less toxic than the available drugs to treat trypanosomiasis with a special focus on sleeping sickness disease.
Keywords: Trypanosoma cruzi; Trypanosoma brucei; flavokawin B; chalcone; trans-splicing; Polygonum ferrugineum; Polygonaceae